2010
DOI: 10.2527/jas.2009-2343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-sulfur water and clinoptilolite on health and growth performance of steers fed forage-based diets1

Abstract: Sulfur-induced polioencephalomalacia (sPEM), a neurological disorder affecting ruminants, is associated with consumption of diets with increased S (high-S). High-S water is commonly found in many western states and is a major source of dietary S for grazing cattle. Consumption of high-S water has been associated with sPEM and decreased performance. Identification of a feed supplement that would counteract the negative effects of high-S water would decrease the incidence of sPEM and prevent performance reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Regrettably, the use of this compound is likely limited by its availability and cost. Others have evaluated the use of clay minerals such as zeolite (Knight et al, 2008) or clinoptilolite (Cammack et al, 2010) as hydrogen sinks to lessen H 2 S production in cattle fed high S diets, but in both cases, the clay mineral had no effects on cattle performance.…”
Section: Other Compoundsmentioning
confidence: 99%
“…Regrettably, the use of this compound is likely limited by its availability and cost. Others have evaluated the use of clay minerals such as zeolite (Knight et al, 2008) or clinoptilolite (Cammack et al, 2010) as hydrogen sinks to lessen H 2 S production in cattle fed high S diets, but in both cases, the clay mineral had no effects on cattle performance.…”
Section: Other Compoundsmentioning
confidence: 99%
“…Besides, this mineral has widespread applications in agriculture [1,2]. According to [38], zeolites also allow better performance of intestinal microflora.…”
mentioning
confidence: 99%
“…Colling et al (1979) observed decreased ADG and DMI in finishing steers fed high-moisture and steam-flaked corn-based diets supplemented with 2.5% bentonite. In other studies (Cammack et al, 2010), supplementation with 2% to 5% clay (as bentonite or zeolite) did not affect ADG, or gain efficiency. Mendel (1971) did not detect differences in DMI between controls and supplemented steers fed 2% to 4% montmorillonite clay.…”
Section: Resultsmentioning
confidence: 65%